How Synthetic Biology and Metabolic Engineering Can Boost the Generation of Artificial Blood Using Microbial Production Hosts - Frost, August T.; Jacobsen, Irene H.; Worberg, Andreas; Martínez, José L. (Frontiers in Bioengineering and Biotechnology, 2018)
Hemoglobin is an essential protein to the human body as it transports oxygen to organs and tissues through the bloodstream (Looker et al., 1992). In recent years, there has been an increasing concern regarding the global supply of this vital protein, as blood availability cannot currently meet the high demands in many developing countries. There are, in addition, several risks associated with conventional blood transfusions such as the presence of blood-borne viruses like HIV and Hepatitis. These risks along with some limitations are presented in Figure 1 (Kim and Greenburg, 2013; Martínez et al., 2015). As an alternative, producing hemoglobin recombinantly will eliminate the obstacles, since hemoglobin-based oxygen carriers are pathogen-free, have a longer shelf-life, are universally com-patible and the supply can be adjusted to meet the demands (Chakane, 2017). A stable, safe, and most importantly affordable production, will lead to high availability of blood to the world popula-tion, and hence reduce global inequality, which is a focus point of the World Health Organization for the millennium (WHO, 2018). Synthetic biology and metabolic engineering have created a unique opportunity to construct promising candidates for hemoglobin production (Liu et al., 2014; Martínez et al., 2016). This review sets out to describe the recent advances in recombinant hemoglo-bin production, the societal and the economic impact along with the challenges that researchers will face in the coming years, such as low productivity, degradation and difficulties in scale-up. The challenges are diverse and complex but with the powerful tools provided by synthetic biology and metabolic engineering, they are no longer insurmountable. An efficient production of cell-free recombinant hemoglobin poses tremendous challenges while having even greater potential, therefore some possible future directions are suggested in this review.